IMPLEMENTASI METODE DEMONSTRASI DALAM PENINGKATAN ATENSI BELAJAR SISWA ADHD - As'ad As'ad (Fakultas Dakwah Universitas Ibrahimy, 2020)
ADHD (Attention Defisit Hyperactivity Disorder) is a child who have attention defisit and hyperactivity disorder.The ability of ADHD in concentraten on a objec and choose the informatoin is low.Learning attention fo ADHD is a effort for improvement the attention or focus to the matheri in class TK Inklusif Star Kids Jember have implemented demonstration method for the solution in that problem. The result show that:1) Demonstratin method is started by the teachers showing the media and discribing the subjec material with the suitable instrument with a RPPH in that day. Then the teachers asked for the ADHD to try and practice it one by one oversightly and controlly; 2) Proponent factors from demosntration method implementation is therapy, parent active action, and the completing instrumes or media visual display. The teachers strategy are therapy fungsion optimally, parenting event ones a mounth, connection book, and completing visual display media; 3)Demonstration method that was implemented in the class is able for improvement attention learning ADHD during 2-3 minutes. This fact is a very good improvement because ADHD can’t to focus although for one minute before